Modelo de simulación para medir el nivel de transformación digital y definir acciones de la estrategia competitiva en la iniciativa clúster metalmecánico del Atlántico (2021)
The country has been implementing a series of initiatives aimed at developing Clusters through competitive routes, with the main objective of improving the competitiveness of the regions. As a result of this process of cluster initiatives, the Metalworking sector of the department of Atlántico began the competitive strategy "Industry 4.0" in 2017, becoming the horizon of work and development of activities to strengthen the cluster. However, for the cluster initiative it has not been an easy process to define and prioritize actions or a clear route to follow; This is due to the novelty of the subject and the lack of information on how to work and intervene in the digital transformation. For this reason, the objective of the research project is to design a simulation model with system dynamics that allows the causal and systematic study of Digital Transformation in this sector, to prioritize factors and define actions that respond to the current need of the cluster initiative and contribute to the Industry 4.0 competitive strategy. The study worked under a 3-phase methodology: 1. Diagnosis, 2. Modeling, 3. Proposal for an action plan. The first phase was based on the characterization of the system and diagnosis of the current state, for which it was necessary to apply additional techniques such as Analytic Hierarchy Process (AHP) and Decision-Making Trial and Evaluation Laboratory (DEMATEL), and a diagnostic instrument of the Transformation level. Digital de Colombia Productiva for data collection in the initiative. The second phase consisted of developing the dynamic hypothesis, the causal diagram of the system and the simulation model, based on the characterization results of the first phase. In the third phase, the results were analyzed and actions were defined for the cluster initiative, for which it was necessary to hold meetings with businessmen who are experts on the subject. Finally, the results show the importance of working on the three key factors of Digital Transformation, prioritizing Digitalization Management, Digital Implementation, and finally Strategic Alignment, this being important for the long-term sustainability of the strategy.